Predicting the "First dose in children" of CYP3A‐metabolized drugs: Evaluation of scaling approaches and insights into the CYP3A7‐CYP3A4 switch at young ages. (28th March 2014) - Strougo, Ashley; Yassen, Ashraf; Monnereau, Claire; Danhof, Meindert; Freijer, Jan
Abstract First‐dose‐in‐children relies on the prediction of clearance from adults for which little information is available on the accuracy of the scaling‐approaches applied. For CYP3A‐metabolized compounds, scaling of clearance is further challenged by different isoforms and by the CYP3A7 to CYP3A4 switch at young ages. This investigation aimed to evaluate the accuracy of two frequently used scaling approaches and to gain insights into the ontogeny of CYP3A. Hence, a literature database was compiled containing 203 clearance values from term‐neonates to adults for 18 CYP3A‐metabolized compounds. The clearances in adults were scaled to children using (i) allometric scaling plus maturation function and (ii) a mechanistic approach based on the well‐stirred model. Three maturation functions were separately evaluated. In children >3 months, all approaches were interchangeable heeding the maturation function applied and biases were mostly observed in children <3 months. The results from a sensitivity analysis indicate that these biases are possibly caused by disregarding the CYP3A7 activity which could account for up to 86% of the metabolism in term‐neonates. Only the mechanistic approach using an overall‐CYP3A maturation function led to unbiased predictions of clearances across all ages. The current investigation adds to the predictions of the first‐dose‐in‐children of compounds (partially) metabolized by CYP3A.